The role of the vagus nerve in hypertonic resuscitation of hemorrhagic shocked dogs - Velasco,I.T. (2004)
Previous studies have suggested a critical role for the vagi during the hypertonic resuscitation of hemorrhagic shocked dogs. Vagal blockade prevented the full hemodynamic and metabolic recovery and increased mortality. This interpretation, however, was challenged on the grounds that the blockade also abolished critical compensatory mechanisms and therefore the animals would die regardless of treatment. To test this hypothesis, 29 dogs were bled (46.0 ± 6.2 ml/kg, enough to reduce the mean arterial pressure to 40 mmHg) and held hypotensive for 45 min. After 40 min, vagal activity was blocked in a reversible manner (0ºC/15 min) and animals were resuscitated with 7.5% NaCl (4 ml/kg), 0.9% NaCl (32 ml/kg), or the total volume of shed blood. In the vagal blocked isotonic saline group, 9 of 9 dogs, and in the vagal blocked replaced blood group, 11 of 11 dogs survived, with full hemodynamic and metabolic recovery. However, in the hypertonic vagal blocked group, 8 of 9 dogs died within 96 h. Survival of shocked dogs which received hypertonic saline solution was dependent on vagal integrity, while animals which received isotonic solution or blood did not need this neural component. Therefore, we conclude that hypertonic resuscitation is dependent on a neural component and not only on the transient plasma volume expansion or direct effects of hyperosmolarity on vascular reactivity or changes in myocardial contraction observed immediately after the beginning of infusion.